Strategi Pemasaran Industri Kecil dan Menengah (IKM) Tahu di Desa Toto Harjo Kecamatan Purbolinggo - Chindy Novita Sari; Eny Ivans; Novita Novita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The tofu IKM is one of the small and medium-sized enterprises that requires development. This is due to the fact that IKM is crucial to economic expansion. The purpose of this study is to develop marketing strategies and analyze the marketing mix for tofu IKM. Given that Toto Harjo Village, Purbolinggo District, is a hub for the tofu business, the study was carried out there. Qualitative descriptive research methodology was employed. Five individuals made up the sample size; they were purposefully chosen based on production requirements of 15–25 kg. According to the study's findings, the product component of the marketing mix is the most crucial. The product is the most crucial component of the marketing mix in this study since it serves as the focal point of all marketing initiatives, with its quality and diversity serving as deciding factors in satisfying customer demands and expectations. The WO strategy is the best marketing approach. The WO strategy is implemented by developing new tofu product varieties and more appealing packaging, participating in SME capital assistance programs, attending training on waste management and tofu production processes, conducting promotional activities and broadening the marketing reach of SMEs, and increasing the capacity of SMEs through SME management training.